PENGARUH KELENGKAPAN INFORMASI LAPORAN KEUANGAN, UKURAN PERUSAHAAN DAN TEKNOLOGI PELAPORAN MELALUI WEBSITE PERUSAHAAN TERHADAP RESPON PASAR SAHAM SYARIAH YANG LISTING DI JAKARTA ISLAMIC INDEX - Muljibir Rahman (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
The aim of this research is to examine the influence of size firm, disclosure index and technologi to expected abnormal return. This research explain whether size firm, disclosure index and technologi to be consideration for investor to respon market. Data in this research are secondary data from companies financial report, daily stock price and IHSG stock price. Research sample are eight companies in JII (Jakarta Islamic Index) at the years 2007-2011, where used purposive sampling method. Panel regression with t test and F test used to test hypothesis. The result show that size firm significant influence to abnormal return, disclosure index doesn’t significant influence to abnormal return, technologi significant influence to abnormal return and size firm, disclosure index and technologi significant influence to abnormal return. From that result, it prove that size firm, disclosure index and technologi make investor imidiately respon the market when financial report published.